PERLINDUNGAN HUKUM KONSUMEN TERHADAP TESTIMONI PALSU DALAM E-COMMERCE DI INDONESIA DAN UPAYA PREVENTIFNYA - Joane Yunizar; Suraji . (Fakultas Hukum Universitas Sebelas Maret, 2025)
This articles aims to analyze preventive measures that can be taken to prevent losses from fake testimonials on Indonesian e-commerce. This research is a prescriptive normative legal research. The research approach used is the statutory approach. Sources of legal materials are obtained from primary legal materials and secondary legal materials by means of literature studies and analyzed using deduction method. The results of the study show that the regulation related to consumer legal protection against fake testimonials on e-commerce activities in Indonesia has not been implemented optimally. The existence of fake testimonials violates the obligations of sellers who are requires to have good intentions in advertising. Therefore, preventive efforts in preventing fake testimonials can be carried out from various parties such as: 1. carrying out verification steps before or after publishing testimonials (for e-commerce parties), 2. being more careful and thorough in making online transactions (for consumers), and making new regulations regarding fake testimonials (for the government).